Effect of confinement on physical inactivity in child and juvenile populations/Efecto del confinamiento sobre la inactividad física en poblaciones infanto-juveniles - Ángel Da Luz Pereira; Maximiliano Tögel; Ximena Campos; Rodrigo Damián Merlo; Manuel Pazos Espín (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: An outbreak of disease due to a variety of coronavirus that affects humans began in December 2019 in Wuhan, China, where as of January 2022 it has caused more than five and a half million deaths. As the COVID-19 pandemic continues to unfold on a global scale, authorities in different territories and countries have introduced various protective measures, including the closure of schools, universities, travel bans, cultural, sporting and meeting, as well as social events. These compulsory social isolation and confinement processes were a reality imposed by the Argentine government as a preventive measure against the SARS-CoV-2 pandemic. Currently, there are few statistical records showing the damage caused to the physical state of child and adolescent populations, which have been confined due to the preventive measures taken against the Covid-19 pandemic. Objective: For this reason, this study aimed to describe some of the effects of confinement on physical inactivity in child and juvenile populations in Comodoro Rivadavia and Rada Tilly. Materials and methods: Scientific research methods and techniques were used, such as analytical-synthetic, inductive-deductive, document analysis and an anonymous questionnaire, answered by 466 subjects (female= 237 - male= 229), whose ages were 12± 6 years. Results: With the data obtained, it was concluded (P<0.05) that this population suffered an increase in the time spent in front of the screens, decreasing the time used to perform physical activity, causing changes associated with an increase in the amount of sleep, due to confinement. Conclusions: This situation will bring consequences in the future; therefore, it is necessary to generate strategies that allow an active environment through physical exercise.